Scientology : the science of truth or the art of deception? (Matthias-Film gGmbH, 2009)
To some, Scientology is a bona fide religion based upon rigorous research with doctrines akin to universal scientific laws. To others, including some former members, Scientology is a cult with so-called doctrines that are nothing more than ridiculous science-fiction stories invented by founder L. Ron Hubbard. Although Scientology is controversial, it is recognized as a legitimate tax-exempt religious organization in the U.S. and in many other countries. However, countries including Great Britain, France, and Germany refuse to grant such status, citing evidence that Scientology's tenets are diametrically opposed to the values of democratic societies.